An Ecological Theory of Free Expression - Chartier, Gary (Springer International Publishing, 2018)
This book advances a comprehensive moral defense of freedom of expression-one with implications for law and policy, but also for the choices of individuals and non-governmental institutions. Gary Chartier seeks to ground expressive freedom in mutually supportive concerns related to themes including property, autonomy, flourishing, and discovery, while seeking to tightly cabin the range of potential injuries that might trigger legal liability for expressive activity. Chartier argues suggestively for an understanding of expressive freedom as rooted and realized in a complex set of social ecosystems that merit protection on multiple grounds and applies it provocatively to a range of contemporary issues.